Infrared radiation and interference on bicameral pacing system - Garcia, Leonardo Rufino; Garzesi, André Monti; Tripoli, Guilherme; Felicio, Marcello Laneza (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
Infrared radiation is used for the treatment of various inflammatory dermatoses. Its use, however, is not described for the treatment of alopecia. We present a case of a bicameral pacemaker carrier since 2014 who used phototherapy for the treatment of this disorder. In the electronic evaluation in June 2017 was diagnosed loss of ventricular sensitivity and command. During surgery, fractures were seen on the electrodes and there was a need for complete system replacement. There are no reports of similar cases in the literature.